Enhanced thermal properties of phase change materials through surfactant-functionalized graphene nanoplatelets for sustainable energy storage - M. Arif, Fikri; Suraparaju, Subbarama Kousik; Mahendran, S.; Pandey, A. K.; Rajamony, Reji Kumar; K., Kadirgama; M. F., Ghazali (MDPI AG, 2023)
Phase change materials (PCMs) are increasingly gaining prominence in thermal energy storage due to their impressive energy storage capacity per unit volume, especially in applications with low and medium temperatures. Nevertheless, PCMs have significant limitations regarding their ability to conduct and store heat, primarily due to their inadequate thermal conductivity. One potential solution for improving the thermal conductivity of PCMs involves the inclusion of nanoparticles into them. However, a recurring issue arises after several thermal cycles, as most nanoparticles have a tendency to clump together and settle at the container’s base due to their low interfacial strength and poor compatibility. To address this challenge, including surfactants such as sodium dodecylbenzene sulfonate (SDBS) has emerged as a prevalent and economically viable approach, demonstrating a substantial impact on the dispersion of carbon nanoparticles within PCMs. The foremost objective is to investigate the improvement of thermal energy storage by utilizing graphene nanoplatelets (GNP), which are dispersed in A70 PCM at various weight percentages (0.1, 0.3, 0.5, 0.7, and 1.0), both with and without the use of surfactants. The findings indicate a remarkable enhancement in thermal conductivity when GNP with surfactants is added to the PCM, showing an impressive increase of 122.26% with a loading of 1.0 wt.% compared to conventional PCM. However, when 1.0 wt.% pure GNP was added, the thermal conductivity only increased by 48.83%. Additionally, the optical transmittance of the composite containing ASG-1.0 was significantly reduced by 84.95% compared to conventional PCM. Furthermore, this newly developed nanocomposite exhibits excellent stability, enduring 1000 thermal cycles and demonstrating superior thermal and chemical stability up to 257.51 °C. Due to its high thermal stability, the composite NePCM is an ideal candidate for preheating in industrial and photovoltaic thermal (PVT) applications, where it can effectively store thermal energy.